Чорнобильська катастрофа та аналіз нормативно-правової бази з питань соціального захисту учасників ліквідації наслідків аварії на ЧАЕС (грудень 1991–2010 рр.) - Бойко, О. (Краєзнавство, 2023)
Мета статті – здійснити системний аналіз нормативно-правової бази з питань соціального захисту учасників ліквідації наслідків аварії на Чорнобильській АЕС, що була впроваджена у правове поле Української держави, починаючи з грудня 1991 по 2010 рр. У статті використано комплекс історичних методів, зокрема аналізу, порівняння, ретроспективи тощо. З’ясовано, що незважаючи на велику кількість різноманітних публікацій щодо Чорнобильської катастрофи та подолання її наслідків, проблематика системного аналізу нормативно-правової бази з питань соціального захисту учасників ліквідації наслідків аварії на Чорнобильській АЕС залишається ще поки малодослідженою. Показано, що джерельною базою дослідження є системоутворюючі закони Верховної Ради України, постанови Кабінету Міністрів України, накази профільних Міністерств щодо соціального захисту ліквідаторів наслідків Чорнобильської катастрофи. Доведено, що аварія на Чорнобильській АЕС стала найбільшою техногенною катастрофою в історії людства та негативно вплинула на суспільно-політичний, економічний та етнокультурний розвиток України. З’ясовано, що у ліквідаторів наслідків аварії на Чорнобильській АЕС внаслідок великих і малих доз радіоактивного опромінення суттєво погіршився стан здоров’я, який негативно позначився на їх працездатності й відповідно вимагав посилення соціального захисту ліквідаторів з боку Української держави. Виявлено, що основні системоутворюючі акти законодавства України (закони Верховної Ради України, постанови Кабінету Міністрів України, накази профільних Міністерств) посприяли визначенню офіційного статусу ліквідаторів наслідків техногенної катастрофи на Чорнобильській АЕС та покращенню їхнього соціального захисту. The purpose of the study is to briefly analyze the causes, the course and the consequences of the Chornobyl disaster and to carry out a systematic analysis of the legal framework on the social protection of the participants of the Chernobyl disaster elimination, which was implemented in the legal field of the Ukrainian state from December 1991 to 2010. In The article used a set of historical methods, including analysis, comparison, retrospectives, etc. It has been found out that despite the large number of various publications on the Chornobyl disaster and overcoming its consequences, the problems of systematic analysis of the legal framework on social protection ofparticipants of the consequences of the Chernobyl disaster remains unclear. It is shown that the source base of the research is the system-forming laws of the Verkhovna Rada of Ukraine, the Decree of the Cabinet of Ministers of Ukraine, the orders of the profile Ministries on social protection of the liquidators of the consequences of the Chornobyl disaster. It is proved that the accident at the Chornobyl NPP became the biggest man-made catastrophe in the history of mankind and had a negative impact on the socio-political, economic and ethno-cultural development of Ukraine. It was found out that the liquidators of the consequences of the accident at the Chernobyl nuclear power plant due to the large and small doses of radioactive radiation significantly worsened the state of health, which negatively affected their efficiency and accordingly demanded increased social protection of the liquidators by the Ukrainian state. It is revealed that the main system-forming acts of the legislation of Ukraine (laws of the Verkhovna Rada of Ukraine, resolutions of the Cabinet of Ministers of Ukraine, orders of the profile Ministries) contributed to determining the official status of the liquidators of the consequences of the technogenic catastrophe at the Chernobyl nuclear power plant and improving their social protection.